Programa Nacional das Escolas Cívico- Militares (2019-2022): regulamentação, adesão e resistências - Tomazini, Amanda Marques (2023)
This research presents an analysis of the National Program of Civic-Military Schools (PECIM), regulated by Federal Decree 10.004/2019 in the period 2019-2022. In order to answer the problem of this research, which is to characterize the process of militarization of public schools proposed by the Bolsonaro Government. Specific objectives were outlined that guided the path taken, namely: to characterize the process of militarization of public schools induced by the Bolsonaro Government, situating the actions of the Ministry of Education and the Ministry of Defense regarding the implementation of Civic-Military Schools; discuss the official documents that regulate PECIM; map adherence to the program at the national level between 2019 and 2022 and catalog documents issued by scientific, legal and social organizations that prove the existence of resistance to PECIM. The study is justified by the need for scientific analysis of this model of educational assistance and its consequences for the field of educational policies and for the formation of children and youth. We seek to discuss the various aspects of this militarized management model, pointing out its incompatibility with the fundamental precepts of educational legislation in Brazil, especially with regard to the necessary defense of public, secular, free schools with socially recognized quality. For this purpose, a qualitative research was carried out through a bibliographic review and document analysis. It results in two chapters: the first discusses the neoconservative neoliberal alliance and its repercussions on educational policies, locating the militarization of public schools within this context; the second characterizes the process of regulation and adherence to PECIM at the national level and also the movements of resistance to the program. The central theoretical foundation adopted includes studies by Apple (2003), Freitas (2018) and Santos (2020).